The Effect of TGT Cooperative Learning on Student Learning Achievement Physics Class XI SMAN 1 Tugumulyo - Eka Maryam (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2018)
This study aims to determine the achievement of physics learning using Teams GamesTournaments (TGT) model and find out an increase or gainscore between experimental classes using TeamGames Tournamens model with control class using whiteboard. Conducting research in SMAN 1Tugumulyo with sample 48 students, consisting of 25 students class XIA1 as experiment class and 23students X1 A2 as control class. The type of this research is quasi experimental design. The data collectiontechnique used is objective test. The statistical prestation test (t-test) used in this research is homogeneoustest and normality data test. The results showed that: 1) the experimental class experienced an increase inlearning achievement between before and after using TGT model, 2) the increase or gainscore in theexperimental class is 5,0 and the gain score of the control class is 4,24. So it can be concluded TGT modelcan affect student achievement.